Clinical features and prognosis of amyotrophic lateral sclerosis in Africa: the TROPALS study. Issue 1 (21st September 2018) - Luna, Jaime; Diagana, Mouhamadou; Ait Aissa, Leila; Tazir, Meriem; Ali Pacha, Lamia; Kacem, Imen; Gouider, Riadh; Henning, Franclo; Basse, Anna; Cisse, Ousmane; Balogou, Agnon Ayélola Koffi; Kombate, Damelan; et al.
Abstract : Objective: We describe and compare the sociodemographic and clinical features, treatments, and prognoses and survival times of patients with amyotrophic lateral sclerosis (ALS) in Africa. Methodology: We conducted a multicentre, hospital-based cohort study in Africa. Patients with ALS diagnosed in the neurology departments of participating hospitals from 2005 to 2017 were included. Subgroup analysis was performed by subcontinent. Survival analyses were conducted using the Cox proportional hazards model. Results: Nine centres from eight African countries participated. A total of 185 patients with ALS were included: 114 from Northern Africa, 41 from Western Africa and 30 from Southern Africa. A male predominance (male to female ratio 2.9) was evident. The median age at onset was 53.0 years (IQR 44.5–64.0 years). The onset was bulbar in 22.7%. Only 47 patients (26.3%) received riluzole, mainly in Northern and Western Africa. The median survival from the time of diagnosis was 14.0 months (95% CI 10.7 to 17.2 months). The median survival was longer in Northern Africa (19.0 months, 95% CI 10.8 to 27.2 months) than in Western (4.0 months, 95% CI 0.8 to 7.1 months) and Southern (11.0 months, 95% CI 5.6 to 16.4 months) Africa (Breslow test, p<0.0001). Both subcontinental location and riluzole treatment independently affected survival. Conclusion: More African patients with ALS were male and younger and exhibited a lower proportion of bulbar onset compared with patients with ALS from Western nations. Survival was consistent with that in Western registers but far shorter than what would be expected for young patients with ALS. The research improves our understanding of the disease in Africa.